Taxation policy and regulation efficiency on increasing zakat collection: countries comparison analysis - Fauzul Hanif Noor Athief; Mohammad Aulia Rachman; Darlin Rizki; Lukmanul Hakim; Mohd Shahid Bin Mohd Noh (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study investigated the policies over countries, specifically concerning the taxation in its regard with the zakat collection. The aim is to see whether making zakat compulsory helps solving zakat collection problem or not.Method - The study used a descriptive analysis model with a qualitative approach. The range of data collected in 2006-2017 came from nine countries, namely Saudi Arabia, Kuwait, Sudan, Jordan, Brunei Darussalam, Malaysia, Indonesia, Singapore, Pakistan.Result - The results of this study indicate that Sudan, Brunei Darussalam, Singapore and Pakistan follow a mandatory approach while Malaysia, Kuwait, Indonesia, Jordan and Saudi Arabia follow a voluntary approach. It was also found that a mandatory approach attracted more zakat collection as indicated by the zakat collection ratio.Implication - Pointing out that mandating zakat by imposing it through regulations helps collect more zakat payments.Originality - This research specifically contributes to studying the tax system in various countries to stimulate the collection of zakat by using a comparative study.